Respuesta :

Answer:

4th option

Step-by-step explanation:

Given

j(x) = [tex]5^{x-3}[/tex] , then

j(x + h) = [tex]5^{x+h-3}[/tex]

[tex]\frac{j(x+2)-j(x)}{h}[/tex]

= [tex]\frac{5^{x+h-3}-5^{x-3} }{h}[/tex] ← factor out [tex]5^{x-3}[/tex] from each term on the numerator

= [tex]\frac{5^{x-3}(5^{h}-1) }{h}[/tex]

The value of j(x+h)-j(x) / h is 5^{x-3}(5^h-1)/h if j(x) = 5^{x − 3} option fourth is correct.

What is a function?

It is defined as a special type of relationship and they have a predefined domain and range according to the function every value in the domain is related to exactly one value in the range.

We have:

[tex]\rm j(x) = 5^{x-3}[/tex]

First fine the value of j(x+h) for this simply plug x+h in the j(x), we get:

[tex]\rm j(x+h) = 5^{x+h-3}[/tex]

Put the values of j(x) and j(x+h) in the below expression, we get;

[tex]=\rm \frac{j(x+h)-j(x)}{h}[/tex]

[tex]=\rm \frac{5^{x+h-3}-5^{x-3}}{h}[/tex]

[tex]=\rm 5^{x-3}\frac{5^{h}-1}{h}[/tex]  or

[tex]=\rm \frac{5^{x-3}(5^{h}-1)}{h}[/tex]

Thus, the value of j(x+h)-j(x) / h is 5^{x-3}(5^h-1)/h if j(x) = 5^{x − 3} option fourth is correct.

Learn more about the function here:

brainly.com/question/5245372

ACCESS MORE